MicroRNA miR-1002 Enhances NMNAT-Mediated Stress Response by Modulating Alternative Splicing - Joun Park; Yi Zhu; Xianzun Tao; Jennifer M. Brazill; Chong Li; Stefan Wuchty; R. Grace Zhai (iScience, 2019)
Summary: Understanding endogenous regulation of stress resistance and homeostasis maintenance is critical to developing neuroprotective therapies. Nicotinamide mononucleotide adenylyltransferase (NMNAT) is a conserved essential enzyme that confers extraordinary protection and stress resistance in many neurodegenerative disease models. Drosophila Nmnat is alternatively spliced to two mRNA variants, RA and RB. RB translates to protein isoform PD with robust protective activity and is upregulated upon stress to confer enhanced neuroprotection. The mechanisms regulating the alternative splicing and stress response of NMNAT remain unclear. We have discovered a Drosophila microRNA, dme-miR-1002, which promotes the splicing of NMNAT pre-mRNA to RB by disrupting a pre-mRNA stem-loop structure. NMNAT pre-mRNA is preferentially spliced to RA in basal conditions, whereas miR-1002 enhances NMNAT PD-mediated stress protection by binding via RISC component Argonaute1 to the pre-mRNA, facilitating the splicing switch to RB. These results outline a new process for microRNAs in regulating alternative splicing and modulating stress resistance. : Biological Sciences; Molecular Biology; Cell Biology Subject Areas: Biological Sciences, Molecular Biology, Cell Biology